Building trust in research through information and intent transparency with health information: representative cross-sectional survey of 502 US adults. (14th June 2022) - Mangal, Sabrina; Park, Leslie; Reading Turchioe, Meghan; Choi, Jacky; Niño de Rivera, Stephanie; Myers, Annie; Goyal, Parag; Dugdale, Lydia; Masterson Creber, Ruth
Abstract: Objective: Participation in healthcare research shapes health policy and practice; however, low trust is a barrier to participation. We evaluated whether returning health information (information transparency) and disclosing intent of data use (intent transparency) impacts trust in research. Materials and Methods: We conducted an online survey with a representative sample of 502 US adults. We assessed baseline trust and change in trust using 6 use cases representing the Social-Ecological Model. We assessed descriptive statistics and associations between trust and sociodemographic variables using logistic and multinomial regression. Results: Most participants (84%) want their health research information returned. Black/African American participants were more likely to increase trust in research with individual information transparency (odds ratio (OR) 2.06 [95% confidence interval (CI): 1.06–4.34]) and with intent transparency when sharing with chosen friends and family (3.66 [1.98–6.77]), doctors and nurses (1.96 [1.10–3.65]), or health tech companies (1.87 [1.02–3.40]). Asian, Native American or Alaska Native, Native Hawaiian or Pacific Islander, Multirace, and individuals with a race not listed, were more likely to increase trust when sharing with health policy makers (1.88 [1.09–3.30]). Women were less likely to increase trust when sharing with friends and family (0.55 [0.35–0.87]) or health tech companies (0.46 [0.31–0.70]). Discussion: Participants wanted their health information returned and would increase their trust in research with transparency when sharing health information. Conclusion: Trust in research is influenced by interrelated factors. Future research should recruit diverse samples with lower baseline trust levels to explore changes in trust, with variation on the type of information shared.